2004
DOI: 10.1002/humu.9297
|View full text |Cite
|
Sign up to set email alerts
|

The mutational spectrum ofENPP1as arising after the analysis of 23 unrelated patients with generalized arterial calcification of infancy (GACI)

Abstract: Generalized arterial calcification of infancy (GACI), is characterized by calcification of the internal elastic lamina of large and medium-sized arteries and stenosis due to myointimal proliferation. Although survival to adulthood has been reported, most patients die within the first six months of life. Recently, we found mutations of ENPP1 coding for ecto-nucleotide pyrophosphatase/phosphodiesterase 1 to be associated with GACI in 8 of 11 families. In this study, we analyzed ENPP1 in affected individuals of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 15 publications
2
87
0
1
Order By: Relevance
“…That ENPP1 functions to inhibit soft tissue calcification is also evidenced by the fact that humans with inactivating mutations in the gene for ENPP1 develop infantile arterial calcification (45,46) and ossification of the posterior longitudinal ligament of the spine (47). Pyrophosphate/phosphate tissue concentration ratios control matrix mineralization, and humans and mice with ENPP1 deficiency have low levels of serum pyrophosphate.…”
Section: Discussionmentioning
confidence: 99%
“…That ENPP1 functions to inhibit soft tissue calcification is also evidenced by the fact that humans with inactivating mutations in the gene for ENPP1 develop infantile arterial calcification (45,46) and ossification of the posterior longitudinal ligament of the spine (47). Pyrophosphate/phosphate tissue concentration ratios control matrix mineralization, and humans and mice with ENPP1 deficiency have low levels of serum pyrophosphate.…”
Section: Discussionmentioning
confidence: 99%
“…12 GACI type 1, the classic form, is caused by mutations in the ENPP1 gene which encodes ectonucleotide pyrophosphatase phosphodiesterase (ENPP1). This enzyme hydrolyses ATP to AMP and inorganic pyrophosphate (PPi), 13,14 the latter molecule being a powerful anti-mineralization factor under normal physiologic conditions. In the presence of loss-of-function mutations in the ENPP1 gene, the synthesis of PPi is reduced leading to reduced PPi/Pi ratio which allows deposition of calcium phosphate complexes to ensue.…”
Section: Introductionmentioning
confidence: 99%
“…8 The patients with GACI type 1 have previously been shown to have a markedly reduced PPi/Pi ratio which would explain the severe mineralization of arterial blood vessels. 13,14 Quite recently, patients with PXE with identified ABCC6 mutations, have also been reported to have reduced plasma PPi/Pi ratio, 11 and fibroblasts from patients with PXE show altered PPi metabolism. 19 These and related observations have led to the suggestion that administration of PPi to the patients could counteract the ectopic mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…A β-thalassemia mouse model showed a significant decrease in ABCC6 protein expression, even if it occurs too late in life and is thus insufficient to promote mineralization [8]. Generalized arterial calcification of infancy (GACI) is a hereditary disorder generally associated with mutations in the ecto-nucleotide pyrophosphatase/phosphodiesterase type I (Enpp1) gene [9]. It was recently reported that some cases of GACI are due to ABCC6 mutations and show characteristic PXE clinical manifestations [10,11].…”
Section: Introductionmentioning
confidence: 99%